Laxative effect of Zengye granule by modulating the SCF/c-Kit pathway and gut microbiota in constipated mice - Lv, Fengxia; Li, Pan; Wang, Bin; Zhao, Menglu; Ji, Peng; Dong, Shishan (Frontiers in Veterinary Science, 2025)
IntroductionZengye granule (ZYG), a traditional Chinese medicine, is listed in the Chinese Pharmacopoeia as a prescription medicine for treating various yin-deficiency diseases including inner heat, dry mouth and pharynx, and dry bound stool. However, the underlying mechanisms of its action remain unclear. This study aimed to assess the laxative effects of ZYG on diphenoxylate-induced constipation in Kunming mice and clarify the underlying mechanism of action of ZYG in treating constipation.MethodsA model of constipation induced by diphenoxylate was developed. The laxative effect was evaluated based on the discharge time of the first black stool, fecal number, fecal weight, intestinal propulsion rate, and intestinal moisture content. Enzyme-linked immunosorbent assay was used to analyze the expression of inflammatory cytokines and neurotransmitters in serum. Histopathological analysis of colon tissues was performed using hematoxylin–eosin staining. Real-time quantitative polymerase chain reaction, immunohistochemistry, and western blotting were used to analyze the mRNA and protein expression of the stem cell factor (SCF)/c-Kit tyrosine kinase (c-Kit) signaling pathway. The composition of the mouse intestinal microbiota was determined by 16S rDNA sequencing.ResultsZYG improved intestinal peristalsis, defecation frequency, and intestinal moisture content. ZYG decreased the abundance of Firmicutes at the phylum and genus levels and increased the abundance of Bacteroidetes at the genus level. ZYG exerted a laxative effect by modulating the SCF/c-Kit signaling pathway.DiscussionThis study provides valuable insights into laxative mechanism of ZYG and its potential veterinary application.